A critical examination of the "China collapse" narrative - Yan Liang (Levy Economics Institute of Bard College, 2025)
Western media and academia have heralded the China collapse narrative. This paper provides a critical and balanced examination of the four challenges facing the Chinese economy - namely, deflation, debt, demographics, and de-coupling/de-risking. It argues that while deflationary pressure is present, consumer demand has been improving as the property market stabilized and policies to bolster domestic demand were and continue to be effective in reflating the economy. China's debt is predominantly internal and semi-public; the central government could leverage up to resolve the local government debt conundrum. A talent dividend and employment optimization could offset the dissipating population dividend; and finally, China's high-quality opening, its participation in the multilateral system and its meaningful engagement with the Global South help counteract the decoupling/de-risking strategies of the US. In sum, while challenges abound, China's sound economic foundations and sensible developmental and macroeconomic policies help to propel economic growth, structural transformation, and green transition.
Keywords: O20; O53; E12; 330; China; Economic Recovery; Public Debt; Government Debt; Job guarantee; Financial Structure; Economic Collapse